Wherefore Art Thou, Medical Textbooks? (GAIMS Journal of Medical Sciences, 2026)
Medical textbooks once formed the intellectual backbone of medical education. Today, their place is increasingly challenged by PDFs, online resources, and AI-driven tools. This editorial explores whether the pursuit of digital convenience risks eroding the depth of understanding essential for safe clinical practice.